Dance and somatics : mind-body principles of teaching and performance - Brodie, Julie A. (McFarland & Co., 2012)
"Training in somatic techniques-- holistic body-centered movement that promotes psycho-physical awareness and well-being--provides an effective means of improving dance students' efficiency and ease of movement. By presenting a philosophical approach to teaching as well as practical instruction tools, this work provides a valuable guide to somatics for dance teachers of any style or level"--Provided by publisher.